Dipole and spin-dipole strength distributions in 124 , 126 , 128 , 130Te isotopes - Çakmak, N.; Çakmak, S.; Selam, C.; Unlu, S. (Springer India, 2018)
We try to present the structure of 1 - excitations in open-shell 124 , 126 , 128 , 130Te isotopes. Electric dipole states are investigated within a translational and Galilean invariant model. Also, a theoretical description of charge-conserving spin-dipole 1 - excitations is presented for the same isotopes. The energy spectra for both kinds of excitations are analysed in detail. Furthermore, a comparison of the calculated cross-sections and energies with the available experimental data is given. © 2018, Indian Academy of Sciences.
Keywords: charge-conserving spin dipole excitations; Translational and Galilean invariance